Social Preferences and Portfolio Choice - Arno Riedl; Paul Smeets (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper explores whether social preferences influence portfolio choices of retail investors. We use administrative investor trading records which we link to decisions of the same investors in experiments with real money at stake. We show that social preferences rather than return expectations or risk perceptions are the main driver of investments in socially responsible (SRI) mutual funds. Social preferences are only associated with investments in SRI funds without tax benefits, but are unrelated to investments in SRI funds with tax incentives. This illustrates that tax incentives change the clientele of mutual funds and that tax incentives crowd out the intrinsic motivations of investors with strong social preferences. Our results also show that prosocial behavior in one domain (experiment) is correlated with prosocial behavior in another domain (investments), which adds to the discussion on the usefulness of experiments in finance.
Keywords: G11; D64; H41; 330; socially responsible investments (SRI); trust game; social preferences; mutual funds